2023
DOI: 10.1111/1346-8138.16801
|View full text |Cite
|
Sign up to set email alerts
|

Impact of body mass index on the severity of bexarotene‐associated hypertriglyceridemia: A post hoc analysis of an open‐labeled clinical study of combined bexarotene and phototherapy in Japanese patients with cutaneous T‐cell lymphoma

Abstract: Bexarotene is an effective oral drug for the treatment of cutaneous T‐cell lymphoma, but careful management is required due to its various side effects. In particular, hypertriglyceridemia often requires a reduction or even suspension of bexarotene therapy. The risk factors of bexarotene‐associated severe hypertriglyceridemia are not clear. Here, we conducted a post hoc analysis of the data from our previous clinical trial, which confirmed the efficacy and safety of combined bexarotene and phototherapy, to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
4
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 30 publications
5
4
3
Order By: Relevance
“…Using a BMI cutoff value of 23.80 kg/m 2 , the sensitivity and specificity were 0.538 and 0.500, respectively. These results differed from our previous findings that suggested that high BMI predicted severe hypertriglyceridemia for all patients and those who received combined bexarotene and phototherapy [13], thus implying that high BMI is a potential risk factor for hypertriglyceridemia and additional unidentified risk factors may exist.…”
Section: Patient Characteristicscontrasting
confidence: 99%
See 4 more Smart Citations
“…Using a BMI cutoff value of 23.80 kg/m 2 , the sensitivity and specificity were 0.538 and 0.500, respectively. These results differed from our previous findings that suggested that high BMI predicted severe hypertriglyceridemia for all patients and those who received combined bexarotene and phototherapy [13], thus implying that high BMI is a potential risk factor for hypertriglyceridemia and additional unidentified risk factors may exist.…”
Section: Patient Characteristicscontrasting
confidence: 99%
“…The BMI cut-off value of 23 kg/m 2 , which was associated with severe bexarotene-associated hypertriglyceridemia in this study, is similar to the criteria for overweight in Asian countries [15][16][17]. As mentioned, our previous study suggested a potential relationship between BMI ≥25 kg/m 2 and severe bexarotene-associated hypertriglyceridemia [13]. These varying results suggested that the BMI cut-off value for severe bexarotene-associated hypertriglyceridemia in Asian countries, including Japan, may be between 23 and 25.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations